Resynchronization of ovulation and conception in nonpregnant dairy cows and heifers - M.A. Portaluppi; D.E. Tenhouse; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2006)
Our objectives were to determine various factors influencing upfront single and multiple ovulation in response to GnRH in a timed arti-ficial insemination (TAI) protocol and subse-quent fertility after altering timing of the sec-ond GnRH injection and AI relative to PGF2αinjection. Replacement heifers (n = 86) and 613 lactating cows previously inseminated were diagnosed not pregnant at biweekly in-tervals to form 77 breeding clusters spanning 36 months. At not-pregnant diagnosis (day 0), females received 100 Î¼g of GnRH, and they received 25 mg of PGF2α7 days later. Females in 2 treatments received GnRH 48 hr (G48) after PGF2αinjection and TAI at the time of the second GnRH injection (G48 + TAI48) or 24 hr later (G48 + TAI72). Females in the third treatment received GnRH 72 hr after PGF2α, when inseminated (G72 + TAI72). Ovaries of females in 65 clusters were scanned at day 0 (first GnRH injection) and 7 days later (PGF2αinjection). Ovarian struc-tures were mapped, and ovulation in response to the first GnRH injection was detected on day 7. When estrus was detected before scheduled TAI, females were inseminated; otherwise TAI conception of remaining fe-males was based on timing of GnRH and AI in 3 treatments. On day 7, 1 or more luteal struc-tures (CL) were detected in 46% of females. Conception rate was 26.5% (98/701) in fe-males that showed estrus and were insemi-nated early. Pregnancy rate was greater in fe-males that ovulated after the first GnRH injec-tion (day 0) and during nonsummer months. Compared with females in late diestrus at nonpregnant diagnosis, cows in early diestrus or those with functional cysts had greater pregnancy rates, but rates were not different from those of cows in proestrus or in metestrus or anestrus. Pregnancy rates did not differ among treatments, but a tendency was detected for a treatment x lactation number interaction. In heifers and first-lactation cows, the G72 + TAI72 treatment produced fewer pregnancies, whereas G48 + TAI48 treatment was least efficacious in older cows. In a TAI protocol for previously inseminated dairy fe-males that are diagnosed not pregnant, subse-quent timed AI pregnancy rates are greater when females are in early diestrus, ovulate in response to the first GnRH injection, or both. (Key Words: Luteolysis, Ovsynch, Ovulation,; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Diary Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Luteolysis; Ovsynch; Ovulation; Pregnancy rate